(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The article forms a position implies the position of the left hand and fingers in one or another part of the fingerboard within one position, the most different positions of the hand and fingers are possible. On the other hand, the same position of the hand and fingers in the same part of the fingerboard can be considered in different positions. The relativity of the concept of position becomes even more obvious when considering numerous examples from violin literature, which use narrowed and expanded finger positions (fifth coverage of the position, decimals, double octaves, etc.).